Covert hepatic encephalopathy: a neglected topic—a narrative review - Mohamed Elbadry; Amin Abdel Baki; Asmaa bakr; Eman A. Elhamrawy; Hayam Abdel-Tawab; Abdelghany Aish; Israa Nooh; Abdulmoneim Adel; Moataz Y. Soliman; Nessren Mohammed; Samy Zaky (Egyptian Liver Journal, 2024)
Abstract Covert hepatic encephalopathy (CHE) is a form of cerebral dysfunction that affects 30–40% of patients with liver cirrhosis as a grave sequel of disease progression. Although being a silent condition, yet; CHE has been reported as seriously predictive for the development of overt hepatic encephalopathy. Covert hepatic encephalopathy is said to conclude grades (0 and 1) hepatic encephalopathy in West Heaven grading of hepatic encephalopathy, hence; inferring to discrete deficits in attention, cognition, and motor control, strongly associated with poorer quality of private and social aspects of the patients’ life. Clinical recognition of cases of CHE is such a tedious task that unluckily devoid of discernment. Worthwhile; the battery of neuropsychometric tests widely known as the only tool to identify CHE can give abnormal results without specifying the cause of brain dysfunction Therefore, dedicated history-taking and clinical evaluation of liver cirrhosis patients are still the cornerstones that should unify other diagnostic tools to identify those patients at risk of developing overt hepatic encephalopathy. Diagnosis of CHE is challenging and often neglected in clinical practice, so the aim of this review is to improve our approach to CHE and begin a unified effort for the advancement of CHE through studying easy, fast, and reliable psychometric diagnostic tests to meet our clinical needs.